Research note: Simultaneous detection of GPV, H5 AIV, and GoAstV via TaqMan probe-based multiplex qPCR - Xiaoquan Wang; Miao Cai; Xiaolong Lu; Qianqian Xu; Yanhong Wang; Wenhao Yang; Kaituo Liu; Ruyi Gao; Yu Chen; Jiao Hu; Min Gu; Shunlin Hu; et al. (Poultry Science)
The endemic status of goose parvovirus (GPV), H5 subtype avian influenza virus (AIV), and goose astrovirus (GoAstV) infections continues to devastate the poultry industry in China. Despite this, there exists a notable gap in the application of molecular diagnostic techniques. This investigation described the development of a multiplex qualitative polymerase chain reaction (qPCR) assay capable of concurrently detecting GPV, H5 AIV, and GoAstV, with no cross-reactivity observed with other avian viral pathogens. The assay exhibited a detection threshold of 10 copies/μL for both GPV and GoAstV, and 1 copy/μL for H5 AIV. The intra- and inter-assay coefficients of variation were < 3.0%, signifying high repeatability within and across assay batches. Utilizing this multiplex qPCR assay, a batch of 60 clinical samples was analyzed to assess its practical utility. The detected prevalence rates for GoAstV, GPV, and H5 AIV were 35.0% (21/60), 21.7% (13/60), and 15.0% (9/60), respectively. Concurrent infections were also identified, with rates for GPV + GoAstV, GPV + H5 AIV, GoAstV + H5 AIV, and GPV + GoAstV + H5 AIV being 6.7% (4/60), 3.3% (2/60), 3.3% (2/60), and 3.3% (2/60), respectively. The developed multiplex qPCR assay exhibited a diagnostic concordance rate equivalent to that of traditional PCR techniques. This novel assay serves as a rapid, efficient, specific, and sensitive tool for the detection of prevalent goose viruses, thereby enhancing disease management strategies and epidemiological monitoring efforts.